The role of artificial intelligence and digital planning in facial surgery - M.D. Prof. Boymurodov Shuhrat Abdujalilovich; Ass. Mamanazarov Akbar Nizom oʻgʻli (Zien Journals, 2025)
In this article, the role of artificial intelligence (SI) and digital planning technologies will analyze in the modern hundred central surgeries. Diagnosis using SI in the study will consider opportunities to improve the operation, surgery accuracy, and ensure sick security. Methods of accurate planning of a hundred structures through 3D modeling, virtual reality and robotable systems will also be illuminated. Featal surgical application of artificial intelligence will not only increase the effectiveness of the surgery, but also provide an individual approach, serve to speed up the rehabilitation process. The article reveals new health approaches by digital surgery
Keywords: Small Intelligence; digital planning; hundred surgery